"WOODEN PRODUCTS IN THE EVERYDAY LIFE OF THE KARAKALPAKS" - Lecturer Doshniyazov Rakhat (Western European Studies, 2025)
This article explores the significance of wooden household items in the daily lives of the Karakalpak people. Wood has historically played a vital role in Karakalpak culture, being used to create essential household objects such as furniture, kitchen utensils, and traditional tools. The craftsmanship of wooden items reflects the community’s artistic heritage, with intricate carvings and patterns often adorning these objects. The study also highlights the sustainable use of natural resources and the traditional techniques passed down through generations. Wooden products not only serve functional purposes but also hold cultural and aesthetic value, showcasing the unique identity of the Karakalpak people.
Keywords: Karakalpaks; wooden household items; traditional craftsmanship